Cyber Security Innovation for the Digital Economy: A Case Study of the Russian Federation - Petrenko, Sergei (River publishers series in security and digital forensics, 2020)
Cyber Security Innovation for the Digital Economy considers possible solutions to the relatively new scientific-technical problem of developing innovative solutions in the field of cyber security for the Digital Economy. The solutions proposed are based on the results of exploratory studies conducted by the author in the areas of Big Data acquisition, cognitive information technologies (cogno-technologies), new methods of analytical verification of digital ecosystems on the basis of similarity invariants and dimensions, and “computational cognitivism,” involving a number of existing models and methods. In practice, this successfully allowed the creation of new entities - the required safe and trusted digital ecosystems - on the basis of the development of digital and cyber security technologies, and the resulting changes in their behavioral preferences. Here, the ecosystem is understood as a certain system of organizations, created around a certain Technological Platform that use its services to make the best offers to customers and access to them to meet the ultimate needs of clients - legal entities and individuals. The basis of such ecosystems is a certain technological platform, created on advanced innovative developments, including the open interfaces and code, machine learning, cloud technologies, Big Data collection and processing, artificial intelligence technologies, etc. The mentioned Technological Platform allows creating the best offer for the client both from own goods and services and from the offers of external service providers in real time. This book contains four chapters devoted to the following subjects: • Relevance of the given scientific-technical problems in the cybersecurity of Digital Economy • Determination of the limiting capabilities • Possible scientific and technical solutions • Organization of perspective research studies in the area of Digital Economy cyber security in Russia.